2010
DOI: 10.1186/1475-2840-9-74
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of coronary artery disease in symptomatic type 2 diabetic patients: evaluation with CT angiography

Abstract: BackgroundCoronary artery disease (CAD) is a common and severe complication of type 2 diabetes mellitus (DM). The aim of this study is to identify the features of CAD in diabetic patients using coronary CT angiography (CTA).MethodsFrom 1 July 2009 to 20 March 2010, 113 consecutive patients (70 men, 43 women; mean age, 68 ± 10 years) with type 2 DM were found to have coronary plaques on coronary CTA. Their CTA data were reviewed, and extent, distribution and types of plaques and luminal narrowing were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
(45 reference statements)
10
20
1
Order By: Relevance
“…Firstly, diabetic patients are more likely to have comorbidities, such as PVD, hypertension, renal impairment, and CVA 26, 27 and our findings support these observations. Secondly, the pattern of coronary artery disease in diabetic patients is usually more extensive and complex compared with non‐diabetic patients 28. This is also evidence from our study of higher rates of MVD in diabetic groups.…”
Section: Discussionsupporting
confidence: 80%
“…Firstly, diabetic patients are more likely to have comorbidities, such as PVD, hypertension, renal impairment, and CVA 26, 27 and our findings support these observations. Secondly, the pattern of coronary artery disease in diabetic patients is usually more extensive and complex compared with non‐diabetic patients 28. This is also evidence from our study of higher rates of MVD in diabetic groups.…”
Section: Discussionsupporting
confidence: 80%
“…This observation is with line with other publications indicating that the most common diseased coronary vessel is the LAD, however to date precise pathogenic mechanism for different susceptibility of different coronary vessels and segments to atherosclerosis is not clear (note that classic cardiovascular risk factors are systemic in nature) [2].…”
Section: Conflict Of Interestsupporting
confidence: 87%
“…Most available data on coronary plaque are based on studies in patients older than 40 years old. These studies demonstrate that plaque is much more common in persons with DM and that the amount of plaque (both calcified or noncalcified) is significantly greater than in the general population (1215). A study by Scholte et al showed that shown that noncalcified plaques were the most common type of plaque found in asymptomatic DM patients who underwent CTAs (16).…”
Section: Discussionmentioning
confidence: 76%